SIOLGA Information Technology Risk Management Analysis Using ISO 31000 - Mamuaja, Hizkia Brayn Minggos; Cahyono, Ariya Dwika (Universitas Bina Darma, 2024)
Salatiga City Disperinnaker, a government agency focusing on industry and labor, has developed the Salatiga Job Vacancy Information System (SIOLGA) to streamline its operations. As the SIOLGA application has recently completed its development phase, there arises a necessity for robust risk management to anticipate potential threats and vulnerabilities. Employing ISO 31000 standards, the research aims to mitigate risks effectively. The ISO 31000 framework encompasses risk identification, analysis, evaluation, and treatment phases. Through this process, the study identified 18 potential risks within the SIOLGA application, categorized into three levels: high, medium, and low. Specifically, there are 5 high-level risks, 10 medium-level risks, and 3 low-level risks. By implementing rigorous risk management strategies, the expectation is for the SIOLGA application to operate more efficiently and optimally, fulfilling its intended objectives.